2015
DOI: 10.1007/s12288-015-0567-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of West Nile Virus Infection in Iranian Blood Donors

Abstract: West Nile virus (WNV) can be transmitted by blood transfusions and organ transplants. This study was a retrospective study which was performed in Blood Transfusion Center to evaluate the WNV infection in blood donors in Iran. A total of 540 blood samples were taken from volunteer healthy donors who referred for blood donation to Chabahar Blood Center. The presence of WNV was studied by detecting immunoglobulin G (IgG) WNV by enzyme linked immune sorbent assay (ELISA). Demonstration of elevated WNV IgG confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Molecular evidence of WNV in mosquitoes accompanied to high IgG seroprevalence in the present study, suggests high WNV circulation in southern Iran. Previous studies performed in some provinces of Iran have shown seropositivity to WNV in humans (ranging from 1.3% to 17.96%), equine (ranging from 2.8% to 23.7%) and birds (15%); however, they did not identify any possible vectors [23, 24,34, 35]. An earlier study in northwest Iran showed the presence of WNV genome in Ae .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Molecular evidence of WNV in mosquitoes accompanied to high IgG seroprevalence in the present study, suggests high WNV circulation in southern Iran. Previous studies performed in some provinces of Iran have shown seropositivity to WNV in humans (ranging from 1.3% to 17.96%), equine (ranging from 2.8% to 23.7%) and birds (15%); however, they did not identify any possible vectors [23, 24,34, 35]. An earlier study in northwest Iran showed the presence of WNV genome in Ae .…”
Section: Discussionmentioning
confidence: 91%
“…From September 2016 to June 2017, a total of 494 leftover serum samples were collected after an agreement with the governmental public laboratories at four major province counties, Khamir, Bandar Abbas, Bashagard and Jask (Fig 1). Sample size was calculated by the expected proportion of positive samples, based on previous studies performed in Iran [24, 29] using 0.05 level of significance resulting in a minimum of 300 samples needed. The samples belonged to people who used the laboratory services for various purposes, for example: routine check-ups, obtaining health certificates, follow ups of their chronic diseases, etc.…”
Section: Methodsmentioning
confidence: 99%
“…None of patients had recent or previous encephalitis symptoms. Although WNV cases and positive serologies have been reported in north and central Iran, [14][15][16] there is no report of WNV from the southern part. YFV has not been reported from Iran, and none of patients were vaccinated against YFV.…”
Section: Discussionmentioning
confidence: 99%
“…An outbreak is reported recently in Karachi however investigator cannot detect the viral genome (Khan et al, 2018). The major routes of transmission is mosquito bites to humans in WNV infection other routes may be blood transfusion and organ transplantation (Aghaie et al, 2016). Diagnoses can be done on the bases of IgM antibodies in blood serum (Control et al, 2011).…”
Section: West Nile Diseasementioning
confidence: 99%